Sero-prevalence of specific Leptospira serovars in fattening pigs from 5 provinces in Vietnam - Hu Suk Lee; Nguyen Viet Khong; Huyen Nguyen Xuan; Vuong Bui Nghia; Hung Nguyen-Viet; Grace, Delia (Springer, 2017)
Background Leptospirosis is a zoonotic bacterial disease with a worldwide distribution. In Vietnam, leptospirosis is considered endemic. In pigs, leptospirosis can result in reproductive problems (such as abortion and infertility) which lead to economic loss. In addition, transmission to people presents a public health risk. In Vietnam, few national studies have been conducted on sero-prevalence of leptospirosis in pigs. The main objective of this study was to evaluate the sero-prevalence and incidence of presumptive infective leptospira serovars in fattening pigs from 5 provinces in Vietnam. Results Blood samples from fattening pigs were randomly collected at slaughterhouses. We collected 1959 sera samples from 5 provinces (Son La, Hanoi, Nghe An, Dak Lak and An Giang) between January and early June 2016. The microscopic agglutination test (MAT) was used to identify the serogroups/serovars. Overall, the sero-prevalence was 8.17% (95% CI: 6.99–9.47) and serovar Tarassovi Mitis (2.19%) had the highest prevalence followed by Australis (1.94%), Javanica (1.68%) and Autumnalis (1.17%) using a cutoff (≥ 1:100). The sero-prevalence among female pigs (5.28%, 95% CI: 3.94–6.93) was slightly higher than among male pigs (4.88%, 95% CI: 3.51–6.58), but this difference was not statistically significant. Conclusions Leptospirosis in pigs may be a useful indicator of the human/animal burden in Vietnam and a risk assessment tool. The presence of some of the identified serovars suggests that wildlife may play an important role in the transmission of leptospirosis to domesticated pigs in Vietnam. Therefore, strengthened monitoring and surveillance systems are needed to better understand the epidemiology of the disease and prevent or reduce infection in humans and animals.